Revitalizing The Quality of Student's Through The Qur'an Recitation Program (Case Study of Students Majoring in Religion MAN 1 Lamongan) - Aida; Junita Putri Indah (Educan : Jurnal Pendidikan Islam, 2023)
Students majoring in religion are required to memorize the Qur'an. Some students are less able to recite the Qur'an fluently, so with that, your program of loving the Qur'an must be applied to students who memorize it, and from Madrasas, it is targeted to memorize at least five juz, even so, not a few students can memorize beyond the target, therefore how revitalizing the quality of students' memorization through the tahsinul Qur'an program. The problem in this research is a). what is the quality of students' memorization at Madrasah Aliyah Negeri 1 Lamongan b). how to revitalize referential quality through the transmigration program at Madrasah Aliyah Negeri 1 Lamongan c). what are the supporting and inhibiting factors for reviving the quality of students' memorization through the Qur'an recitation program at Madrasah Aliyah Negeri 1 Lamongan. This research includes descriptive where researchers seek more in-depth information with this type of case study research. Researchers get data through observation, question, and answer, supported by photographs. Informants in this study consisted of Madrasah heads, heads of religious programs, tahsin teachers, and students. Based on the research results, it was found that: a). the reading quality of students who were initially unstable experienced a significant increase after participating in the reading improvement program in the tahsin class b). the teacher's efforts to improve the quality of students' memorization through the tahsinul Qur'an program emphasize intention, motivate students, tahsin al-Qur'an with ummi method, and talaqqi c). the supporting factors are Madrasah policies, teachers have skill in the field of knowledge of the al-Qur'an with the qualification of hafidz-hafidzah, there are tashih and tasmi' activities, student's enthusiasm, and facilities. As for the obstacles, there are very limited abilities, no discipline, laziness, and too much learning content.